The nature of education for Edgar Morin - Lecturer Alaa Hamid Rasheed Al-Halbousi, Assist Prof. Dr. Mohammed Abdullah Al-Khalidi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The basic subject of the philosophy of education is the human being, and it is the basic goal of education itself, and the answer to any educational question that is ultimately subject to our continuing philosophy in life, as every system has goals, and the goal of education stems towards the human community, and philosophers and thinkers of education work to formulate multiple images of the goals of life and education goals. The subject of education is one of the most important topics studied of contemporary thought, including what was proposed by our philosopher Morin, as the philosophy of education occupied a distinguished place in his writings, and he submitted his book to UNESCO under the title: (The Nature of Education) in which he expresses his views on the essence of education in the context of his vision of knowledge unity, as a new future method that directs education towards sustainable development, Morin has presented seven principles as keys as he considers it necessary for future education.